STUDI EKSPERIMEN PENGARUH JUMLAH BLADE PENGADUK TERHADAP KUALITAS BIODIESEL YANG DIHASILKAN DARI MINYAK JELANTAH - Drajat Indah Mawarni (SIMETRIS, 2017)
Biodiesel is an alternative material that is environmentally friendly, has no effect on health and can be used as fuel for motor vehicles. The raw material for making biodiesel uses raw cooking oil with KOH catalyst, the research conducted using the number of blades, namely 4 blades, 6 blades and 8 blades. The purpose of this study was to determine the effect of the number of blades on the quality of biodiesel which includes calorific value, viscosity, density, flash point, pour point produced from waste cooking oil. Variation in the number of 4 blades, 6 blades, and 8 blades with a stirring process for 1 hour at 100 rpm rotation. The results of research that have been done are variations in the number of blades affect the quality of biodiesel produced, this is evidenced that from the number of blades 8 produces a heating value of 17.46 46 Btu / lb. Making a difference between blade 8 with 6 yields a difference of 0.14 Btu / lb and blade 8 with 4 produces a difference of 0.28 Btu / lb